A pilot study of oral calcitriol (1,25-dihydroxyvitamin D3) for relapsing-remitting multiple sclerosis. - Wingerchuk, D; Lesaux, J; Rice, G; Kremenchutzky, M; Ebers, G (2005)
BACKGROUND: Epidemiological and ecological studies suggest links between vitamin D deficiency and increased multiple sclerosis (MS) prevalence. OBJECTIVE: To evaluate the safety and tolerability of oral calcitriol therapy in an open label pilot study. METHODS: 15 ambulatory patients with relapsing-remitting MS and at least one clinical relapse within the previous 12 months received oral calcitriol (target dose: 2.5 microg/d) for 48 weeks. Dietary calcium was restricted to 800 mg/d. Patients were monitored using frequent clinical and laboratory examinations, the expanded disability status scale (EDSS), and brain magnetic resonance imaging (MRI). RESULTS: Two patients withdrew because of symptomatic hypercalcaemia (serum calcium >3.35 mmol/l in each case) resulting from persistent dietary indiscretion. Two diet compliant patients required temporary dose adjustments for mild asymptomatic hypercalcaemia. Diet compliant patients experienced mild adverse effects. The on-study exacerbation rate (27%) was less than baseline. Four patients experienced five clinical relapses but only one patient worsened by >1 EDSS point. Brain MRI revealed enhancing lesions in five patients at baseline (33%) and in four (29%) at both 24 and 48 weeks. CONCLUSIONS: Oral calcitriol is safe and well tolerated for up to one year by diet compliant relapsing-remitting MS patients. Further study of vitamin D related mechanisms is warranted in MS.